LASERS : Lasing on the 4I13/2 → 4I15/2 transition of Er3+ ions in ZrO2 – Y2O3 – Er2O3 crystals under resonant diode pumping into the 4I13/2 level. (1st June 2016) - Ryabochkina, P A; Sidorova, N V; Chabushkin, A N; Lomonova, E E
Abstract: Experimental results on lasing in ZrO2 – Y2 O3 – Er2 O3 crystals are presented. Under diode pumping of ZrO2 – Y2 O3 (13.8 mol %) – Er2 O3 (0.2 mol %) crystals into the 4 I13/2 level of Er 3+ ions, lasing is obtained at the 4 I13/2 → 4 I15/2 transition with a wavelength of 1648 nm.